2016
DOI: 10.1038/nnano.2016.135
|View full text |Cite
|
Sign up to set email alerts
|

Improving the efficacy and safety of biologic drugs with tolerogenic nanoparticles

Abstract: The development of antidrug antibodies (ADAs) is a common cause for the failure of biotherapeutic treatments and adverse hypersensitivity reactions. Here we demonstrate that poly(lactic-co-glycolic acid) (PLGA) nanoparticles carrying rapamycin, but not free rapamycin, are capable of inducing durable immunological tolerance to co-administered proteins that is characterized by the induction of tolerogenic dendritic cells, an increase in regulatory T cells, a reduction in B cell activation and germinal centre for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
183
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(193 citation statements)
references
References 49 publications
4
183
0
1
Order By: Relevance
“…Interestingly, although PLG is highly biocompatible, it can lead to inflammatory responses, [35,36] which is consistent with some of the results seen here. Despite this, several recent studies have demonstrated that PLG nanoparticles could be successfully used to induce tolerance in models of autoimmunity and allergy [1214,37,16,17] . One strategy involves administering ~500nm particles loaded with antigen (either surface conjugated or encapsulated) by an intravenous (i.v.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, although PLG is highly biocompatible, it can lead to inflammatory responses, [35,36] which is consistent with some of the results seen here. Despite this, several recent studies have demonstrated that PLG nanoparticles could be successfully used to induce tolerance in models of autoimmunity and allergy [1214,37,16,17] . One strategy involves administering ~500nm particles loaded with antigen (either surface conjugated or encapsulated) by an intravenous (i.v.)…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several promising nanoparticle-based tolerogenic therapies have been reported. [1217] These technologies are based on nanoparticles that are loaded with antigen alone [1214] or with tolerogenic factors [1517] and administered intravenously (i.v. ), following which they are taken up by splenic antigen presenting cells (APCs) and processed through tolerogenic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…In one example, PLGA NPs were used for intravenous and subcutaneous delivery of rapamycin to induce tolerance against coadministered model antigens [75]. These NPs targeted rapamycin selectively to APCs, in contrast to free rapamycin that was distributed systemically, acting on multiple cell types.…”
Section: Biomaterials Improve Targeting Selectivity and Potency Of mentioning
confidence: 99%
“…They co-administered the coagulation factor VIII together with the immunosuppressive agent rapamycin loaded into PLGA NPs and observed promising in vivo results in terms of maintaining the efficacy of the biologic entity in an hemophilia A mice model [154]. In their search for a more universal approach, they explored the interest of co-administering rapamycin-loaded PLGA NPs together with different proteins (OVA, pegsiticase, adalimumab) and the results showed durable inhibition of ADAs formation [310]. Currently, patients are being recruited for a phase II clinical trial for the evaluation of the co-administration of rapamycin-loaded PLGA NPs with free pegsiticase: a pegylated uricase enzyme implicated in the metabolization of uric acid, that is currently administered for the treatment of hyperuricemia and chronic gout [311].…”
Section: The Next Challenge In Immunomodulation: Overcoming Antidrmentioning
confidence: 99%